Using crossmodal correspondences as a tool in wine communication - Crichton-Fock, Anders; Spence, Charles; Pettersson, Nicklas (Frontiers in Psychology, 2023)
This research investigates consumer acceptance of alternative methods for communicating information about wine, focusing on the alignment between sensory attributes and consumer expectations. A survey was administered to wine enthusiasts to assess their attitudes toward crossmodal communication. The findings reveal significant associations between consumer behaviors and acceptance of alternative communication methods, highlighting the emerging field of crossmodal correspondence. These results suggest that leveraging crossmodal correspondence can enhance the match between a product's sensory qualities and consumer expectations, potentially reducing wine wastage resulting from unmet consumer preferences. These findings have implications for improving communication strategies in the wine industry and enhancing consumer experiences.